Nanocrystalline diamond coatings: Effects of time modulation bias enhanced HFCVD parameters - Abbas Hodroj (AIMS Materials Science, 2018)
Nanocrystalline diamond NCD coatings could improve the performances of cutting tools if the adhesion on cobalt-cemented tungsten carbide WC–Co substrates was optimized and maintained during diamond deposit. In this study, a time modulated polarized growth process during diamond hot filament chemical vapor deposition (HFCVD) method was used. NCD coatings were deposited on cobalt-cemented tungsten carbide (WC–10% Co) substrates previously coated with tantalum or zirconium nitride–molybdenum bilayer as interlayer systems to control carbon and cobalt diffusion. Continuous films consisted of diamond clusters. Their size decreased when the applied bias voltage increased and substrate temperature decreased. Raman analyses confirmed the reduction of crystallite size and formation of nanocrystalline diamond films by time modulated biased substrate HFCVD process. Scratch tests showed that the NCD/interlayer systems/WC–10% Co displayed very good film adhesion interesting for cutting tools applications compared to NCD/WC–10% Co. In addition using an interlayer system could offer additional protection when diamond coating was deteriorated. This technique seems to be promising for industrial applications in the field of machining tools when increasing the thickness of the diamond layer by only extending the time modulated deposition process.